Changes in the Quality of Life of Medical Students at a Private University in Anápolis, Goiás (CIPEEX, 2025)
Medical students face a heavy workload that changes throughout the course, forcing them to cope with sleepiness to complete their activities, which negatively impacts their quality of life. The objective of this study is to describe the relationship between medical training and the quality of life of medical students at a private university in Anápolis, Goiás. This is a quantitative, exploratory, descriptive study conducted with students from the 1st to the 8th semester, using the WHOQOL-BREF questionnaire and sociodemographic data. A total of 330 questionnaires were collected, of which 236 were analyzed. Most respondents were women (65.3%), white (75.0%), single (97.9%), and reported a family income above five minimum wages (63.1%). In the WHOQOL-BREF analysis, the averages remained stable, except in the 5th period, when there was a sharp drop in all domains evaluated. In addition, when correlating the WHOQOL-BREF scores with sleep, age, and the social and mental domains, it was observed that older students reported poorer quality of life. Thus, sociodemographic factors proved decisive in characterizing the sample, which is influenced by academic routine. However, despite variations in students’ well-being, no significant reductions were observed in overall quality-of-life scores.
Keywords: Quality of Life; Sleep; Student Health; Medical Students